Kebijakan Pemerintah dalam Memberikan Perlindungan Hukum Bagi Penata Anestesi yang Bekerja Tanpa Dokter Spesialis Anestesi - Widigdo Rekso Negoro (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The availability of anesthesiology specialists in Indonesia remains disproportionate to the growing demand for health services. This condition compels nurse anesthetists to play a crucial role in delivering anesthesia services, particularly in hospitals that lack anesthesiology specialists. This study aims to analyze the form of legal protection for nurse anesthetists who perform anesthesia practice in hospitals without anesthesiology specialists and to assess the alignment between existing regulations and actual field conditions. This research employs a normative juridical approach with a descriptive-analytical method, examining primary legal materials such as laws and ministerial regulations, along with secondary materials including academic literature and scholarly journals on health law. The analysis focuses on identifying gaps between the legal framework and the professional practices of nurse anesthetists in hospitals. The findings reveal a significant discrepancy between normative regulations and the practical needs of medical services. Existing laws, including Law No. 17 of 2023 and Minister of Health Regulation No. 18 of 2016, do not provide sufficient legal protection for nurse anesthetists working without direct supervision. Consequently, they face legal risks in performing their duties, even when their actions are aimed at ensuring patient safety. The study concludes that reform of health law policies is urgently needed to adapt to current service conditions, particularly through the establishment of clearer delegation mechanisms and indirect supervision systems. These findings contribute to the development of health law literature in Indonesia and serve as a foundation for future research on the implementation of legal protection for nurse anesthetists.